Morfologia comparada do estômago e da junção gastroduodenal de morcegos da família Phyllostomidae (Mammalia, Chiroptera) - Rozensztranch, Andréa Melo da Silva (2004)
Comparative morphological study of the stomach and the gastroduodenal junction is undertaken in 12 genera of bats representing five sub-families of the family Phyllostomidae. We dissected and prepared histological sections of the stomach and gastroduodenal junction of 80 microchiropteran specimens. Standard staining and histochemical procedures were employed. Sections were examined under light microscopy and photomicrographies were taken using a video microscope. Line drawings were made for recording gross morphological variations, which indicate that five macro categories are identifiable: Hematophaga, Simple-sacular, Sacular, Intermediate-sacular, and Com pie xsacular. We identified four regional gastric pattems of the rugae (longitudinal and parallel, undulated and parallel, complex and interdigitating, and finally tortuous and ana~tomosed) as well as two pyloric sphincter types. Histological results show that the typical cellular types vary regionally within the gastric mucosae and principally in the fundic glands among genera and between sub-families. The fundic glands of Desmodontinae showed the shallowest depth and the least number of cells. Three pattems of villi morphology (digitiform, foliaceous and pyramidal) are recognized at the gastroduodenal junction. The Brünner' s gland is present at the submucosa of the gastroduodenal j unction in almost all Phyllostomidae except Uroderma and Platyrrhinus. The histochemistry demonstrates differences between the distribution of glycoproteins and proteoglycans which can be possibly related to diet representing adaptations to it. This is the first detailed study of the distribution and characterization of elastic and collagenous fibers in the stomach wall. The distribution of the enteroendocrine cells is also described. Cladistic evaluations of the information content of phyllostomid digestive system indicate quite promising results.